Comfort After Abdominal Surgery: Systematic Review - ÇİFTÇİ, Hatice; KORKUT, Sevda (Göbeklitepe Medical Science Journal, 2024)
This study was conducted to investigate the postoperative comfort of patients undergoing abdominal surgery. Data were obtained by searching Pupmed, WOS, Scopus databases on June 23, 2023 using the keywords “abdominal surgery” and “comfort”. As a result of the search, 889 articles were reached and the articles were examined independently by the researchers. In total, 14 articles were examined in terms of inclusion criteria and 4 articles were included in the study. Of the articles on the change in comfort status with nonpharmacologic interventions before and after surgery in general surgery patients undergoing abdominal surgery, 75% were from nursing and 25% were from general surgery. 50% of the articles were conducted in China and 75% were randomized controlled trials according to research design. 50% of the studies applied acupressure from complementary treatment methods, 25% applied oral carbohydrate intake before surgery and 25% applied a warming care protocol in hypothermia after abdominal surgery. The interventions identified had a positive effect on the comfort of the patients. In order to increase the comfort of the patient group undergoing abdominal surgery, it may be recommended to plan nonpharmacologic interventions and conduct research supported by comfort scales.